OPTICAL COHERENCE TOMOGRAPHY PREDICTS VISUAL RECOVERY OF PATIENTS WITH PITUITARY ADENOMA FOLLOWING SURGERY IN DR KARIADI HOSPITAL,SEMARANG - Nitihapsari, Galuh Yulieta; Prihatningtias, Riski (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction and Objective: The characteristics, symptoms, and clinical manifestations of pituitary adenoma in Indonesia have not been widely studied. In 26 patients undergoing pituitary surgery at Dr. Kariadi Hospital, we compared visual acuity pre-operative and post-operative from normal and thin optical coherence tomography (OCT) of the retinal nerve fiber layer (RNFL) and ganglion cell layer-internal plexiform layer (GCL-IPL). Method: A retrospective study of the medical record from January 2020 to December 2022 was done. 21 of the 26 patients had surgery by the transsphenoidal route and the rest by craniotomy. All patients had macroadenoma (tumor size >1cm) and were histologically confirmed. Visual acuity before and after surgery was evaluated along with the patient’s OCT value. Result: The thinner pre-operative RNFL thickness was associated with worse visual acuity (VA). Patients with normal RNFL had a median VA of 20/200 while those with thin RNFL had to count their fingers (CF). The patients with normal pre-operative RNFL had a significant improvement in median VA after surgery, from 20/200 to 20/32 (p=0.022), whereas the patients with thin RNFL did not improve (CF to CF, p=0.026). The patients with normal pre-operative GCL-IPL had non-significant improvement in median VA after surgery from CF to 20/20 (p=0.505), also the patients with thin GCL-IPL from CF to 20/200 (p=0.151). Conclusion: The visual recovery after pituitary adenoma surgery is likely to be predicted by pre-operative OCT RNFL. Patients with normal RNFL thickness show an increased tendency in visual recovery after surgery. Keywords: Optical coherence tomography , visual acuity, pituitary adenoma